Environmental design research in Russian architecture: Western roots and national forms of existence. (15th July 2019) - Kiyanenko, Konstantin
Abstract : Purpose: The topics "environment, " "environmental design" and "environment and behavior studies" are important and promising in architectural discourse. The academic culture of the global west plays a unique role in the development of the knowledge within the field of environmental design research (EDR), from which these concepts originate. This paper examines the western names, works and ideas related to EDR that have spread into Russian architectural discourse. The purpose of this paper is to consider the status quo of Russian knowledge of EDR and its connection with the western EDR tradition. Design/methodology/approach: The method of research in this paper is the analysis of references and keywords of architectural publications from the largest Russian academic online library – e-library.ru. Findings: The origin, evolution and current state of environmental architectural knowledge in Russia are discussed. Its segmentation including the presence of several self-organized spheres within the EDR domain and the variety of "dialects" of environmental language are illustrated. The connections of each segment of Russian knowledge with western authors and sources are traced. Further, conclusions are drawn regarding the similarities and differences between Russian and western knowledge in the field of EDR. Originality/value: The relationship of Russian architectural theory with western EDR knowledge has not previously been the subject of a comparative scientometric study.